Planning and Executing A Health Sciences Campus IPE Day - Jacquelyn Fried; Lisa Lebovitz (Association of American Medical Colleges, 2013)
Abstract The purpose of this article is to describe the facilitators, planning, execution and lessons learned from this inaugural event. A detailed account of the work plan and campus and administrative infrastructural facilitators is provided. Event programs and flyers are attached to offer templates for others to study and/or modify for their own usage. Health professions' academic institutions are encouraged to embrace IPE. This submission describes a health sciences campus' first IPE Day and delineates its planning and implementation phases and shares the lessons learned. Forces that facilitated the development and execution of IPE Day are discussed and supportive program materials are provided to share with the readership. It is hoped that this example of a health sciences university's campus wide IPE Day will serve as a resource to others and will encourage and motivate them to attempt similar IPE events on their respective campuses.